Hungry corporations : transnational biotech companies colonise the food chain - Paul, Helena (Zed Books in association with Econexus and the Pesticide Action Network Asia-Pacific (PAN-AP) ; Distributed in the USA exclusively by Palgrave, 2003)
This work provides a detailed account of how huge agrochemical corporations have come to control the food chain, exposing their influence over governments, regulatory bodies and university research. It examines how a handful of companies have: accelerated the industrialization of agriculture and the integration of the global economy; penetrated the previously independent world of scholarly research in universities and specialized agencies; manipulated public opinion and distorted our understanding of key environmental processes and issues; unduly influenced regulatory agencies and national governments; pushed the WTO, World Bank and FAO towards policies favouring corporate growth and profit; an bullied the governments and farmers of the developing countries to accept their technologies and products.